1987
DOI: 10.1152/ajpgi.1987.253.3.g298
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory action of peptide YY on gastric acid secretion

Abstract: The purpose of this study is to investigate the effect of peptide YY (PYY) on pentagastrin-, histamine-, and bethanechol-stimulated gastric acid secretion and the possible mechanisms by which PYY inhibits gastric acid secretion. Six mongrel dogs with chronic gastric and duodenal fistulas were given an intravenous infusion of pentagastrin (0.5 microgram . kg-1 . h-1), histamine (18 micrograms . kg-1 . h-1), or bethanechol (80 micrograms . kg-1 . h-1) either alone or simultaneously with intravenous PYY (100, 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

1990
1990
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 0 publications
0
27
0
Order By: Relevance
“…Intracerebroventricular injection of PACAP stimulates gastric acid secretion (Ozawa et al, 1997), sug-324 gesting that PACAP may act centrally to regulate gastric acid release. The central effect of PACAP may involve peptide tyrosine tyrosine (PYY) as an indirect mediator (Guo et al, 1987), because intravenous injection of PACAP has been shown to increase plasma PYY concentrations . In the antrum of mammals, PACAP regulates locally the secretion of a number of peptides, including atrial natriuretic peptide (Gower et al, 2003), gastrin, and somatostatin (Tornøe et al, 2001).…”
Section: F Effects Of Pituitary Adenylate Cyclase-activating Polypepmentioning
confidence: 99%
“…Intracerebroventricular injection of PACAP stimulates gastric acid secretion (Ozawa et al, 1997), sug-324 gesting that PACAP may act centrally to regulate gastric acid release. The central effect of PACAP may involve peptide tyrosine tyrosine (PYY) as an indirect mediator (Guo et al, 1987), because intravenous injection of PACAP has been shown to increase plasma PYY concentrations . In the antrum of mammals, PACAP regulates locally the secretion of a number of peptides, including atrial natriuretic peptide (Gower et al, 2003), gastrin, and somatostatin (Tornøe et al, 2001).…”
Section: F Effects Of Pituitary Adenylate Cyclase-activating Polypepmentioning
confidence: 99%
“…The viewpoint of Pappas et al [65] was further confirmed by later studies in dogs [30] and rats [35]. In fasted rats, administration of PYY (3.2 nmol/kg/h, iv) had no effect on bethanechol-induced acid output, however, it inhibited baclofen-induced acid output by 61.8%, which was more potent compared with the inhibition on pentagastrinand histamine-induced acid output [35,36].…”
Section: Pyy Is More Potent To Inhibit Gastric Acid Secretion Inducedmentioning
confidence: 82%
“…PYY and PYY are the two molecular forms of PYY abundant in the blood [25]. The PYY derivatives [Leu 31 , Pro 34 ] PYY (or Pro 34 PYY) and PYY (or PYY show selective affinity to Y1 and Y2 receptors respectively [6]. Circulating PYY displays a profound inhibitory action on gut motility, gastric emptying and acid secretion as well as pancreatic exocrine secretion [32,62,64,65].…”
Section: Introductionmentioning
confidence: 99%
“…Peptide YY (PYY) and enteroglucagon are synthesized by L-type endocrine cells in the distal ileum and colon and have been shown to inhibit several gut functions including acid secretion (Adrian et al, 1985;Guo et al, 1987a;Pappas et al, 1986;Sheikh, 1991;Walsh, 1994). Considering the location of L cells in the distal gut, PYY and enteroglucagon may participate in the modulation of transit times, gastric and pancreatic secretion, and nutrient absorption (Goodlad et al, 1991).…”
Section: Discussionmentioning
confidence: 99%